Economic Significance of Agriculture for Poverty Reduction: The Case of Zambia - , Libanda Juliet; , Nkolola Barbara; , Nyasa Linda (Archives of Current Research International, 2016)
As a developing nation, Zambia has a number of setbacks to its economic development. One adverse setback that has affected the country’s economic development pursuits is poverty. The economy of Zambia has faced some draw backs and domestic distress has increased, making it very difficult for the country in its pursuit for sustainable development. This study analyzes Zambia’s main strategy of poverty eradication: agriculture. The study investigates the status and contribution of agriculture to the economy of Zambia. The results show that agriculture is the second largest contributor to the GDP of the country. Further, results indicate that there is heavy reliance on maize production than any other food crop in the country. These results can be used for policy formulation and economic projections in order to significantly contribute to poverty reduction in Zambia.